Study on Mechanism and Control Technology of Asymmetric Floor Heave in a Deep Soft Rock Main Roadway - Fulian He; Wenli Zhai; Xuhui Xu; Jiayu Song; Liang Li; Kai Lv (Geofluids)
Considering the serious asymmetric deformation and failure of the floor of 1# main roadway in Wanglou Coal Mine, the mechanism of roadway asymmetric floor heave was studied through on-site investigation, theoretical analysis, numerical simulation, and on-site test. The following conclusions were drawn: (1) the floor heave of 1# main roadway is mainly caused by high original rock stress, surrounding rock stress, water physical effect, support strength, etc. (2) A mechanical model of asymmetric floor heave is built and analyzed. Roadway floor stability is relevant to the stress concentration coefficient of the roadway sides, the burial depth of the roadway, and the cohesion and internal angle of friction of the floor rock. The relationship between the upward resultant force of the floor and the stress concentration coefficient of the roadway sides is established. Affected by mining, the upward force of roadway floor reaches 17.0 MPa, and serious floor heave is easy to occur when the floor is opened. (3) The floor heave curve of the position of 1# main roadway corresponding to working face is obviously asymmetric, the maximum value of floor heave being 948 mm. The floor heave curve of other positions of 1# main roadway is basically symmetric, the maximum floor heave value being merely 497 mm. A new “differentiated” combined support is proposed and field tested. It has been 13 months since the completion of main roadway repair in this section, no obvious deformation occurred, and the long-term stability of soft rock roadway support in deep mines is realized.